ANALYSIS OF INVESTMENT AND DEVELOPMENT BANKS' EFFICIENCIES AN APPLICATION IN TURKISH BANKING SECTOR (Third Sector Social Economic Review, 2019)
Development and investment banks contribute to the creating and development of capital markets in developing countries. They pioneer the development of capital markets by supporting industrialization, technical consultancy, participating in the improvement process of companies and realizing public offerings. The biggest obstacle to developing countries is the low level of income and the resulting inadequate savings. To overcome these problems, developing countries have established development and investment banks. The effective work of these banks, which add value to the country's economy, is important both for the country it is located and for the bank itself. In our study, shown that the performance of the between 2013-2017 years of ongoing development and investment banks operating in Turkey which are calculated with using data envelopment analysis relative efficiency scores. According to the results, most of the investment and development banks between the years 2013-2015 showed effectiveness. On the other hand, banks with low efficiency increased their efficiency scores especially in 2016.
Keywords: Investment Banks; Development Banks; DEA Analysis